Osteoporosis: From Bone Biology to Individual Treatment Decision - Maria João Gonçalves; Ana Maria Rodrigues; Helena Canhão; João Eurico Fonseca (Acta Médica Portuguesa, 2013)
Introduction: Osteoporosis is a bone metabolic disease with increasing prevalence in ageing societies. Herein we reviewed recent epidemiologic findings and their impact in the individual patient management. In addition we dissected the major disease mechanisms which have uncovered new potential therapeutic strategies. Material and Methods: Using MeSH terms (osteoporosis, epidemiology, Portugal, Europe, pathogenesis, osteoblasts, osteoclasts, osteocytes, immune system, obesity, therapy, randomized controlled trial, efficacy, safety) as keywords. We have reviewed original studies, reviews and position papers indexed in PubMed. Results: Osteoporosis is increasingly prevalent, but recently an age-adjusted rate of fracture plateau was reached. A new fracture risk assessment tool was developed, FRAX™, which integrates the contribution of clinical risk factors associated with fragility fractures. It can be used either independently or in combination with bone mineral density. Osteoporosis treatment is offered only to a fraction of the affected individuals. In addition, 40% of the patients receiving Osteoporosis medication had a previous fracture. Relevant safety issues of different drugs used in Osteoporosis have been detected in post-marketing experience. Finally, advances in the understanding of the molecular pathways involved in Osteoporosis led to the development of new drugs. Discussion and Conclusion: Despite the existence of diagnostic tools and several effective treatments, Osteoporosis treatment is still offered only to a fraction of the affected individuals and mainly to a population with advanced disease. New and more effective treatments might change this scenario.